Assessment of bio-nanoemulsion seed priming on sucking pest management and vigor enhancement in cotton - Vishnu, M; Kannan, M; Soundararajan, R P; Suganthi, A; Subramanian, A; Senthilkumar, M; Rameash, K; Samyuktha, S S; Dineshkumar, S; Prithiva, J N; Madesh, K; Indhumathi, P (Plant Science Today, 2025)
Cotton (Gossypium spp. L.) is the most important natural fibre crop. Various sucking pests, including aphids, jassids, whiteflies and thrips, often constrain its productivity. Seed treatment is recognized as a vital strategy for managing these pests, thereby reducing the need for repeated foliar insecticide applications. The azadirachtin nano emulsion (NE) was prepared using azadirachtin (1 % w/v), 1 % chitosan (50 % v/v) and 5 % (v/v) neem oil as key components. In this study, we evaluated the effect of an azadirachtin-based polymer NE (NE 1 %) for its effects on seed germination and early-season pest suppression under both laboratory and field conditions. The optimised NE exhibited a mean droplet size of 159.4 nm and a low polydispersity index (PDI = 0.189), indicating good stability and uniformity. Laboratory assays revealed that application of NE at 10 mL kg-1 significantly enhanced germination (72 %) (p < 0.003) and vigor index (2434.47) (p < 0.002) outperforming thiamethoxam and water priming. In contrast, under field trials, thiamethoxam 25 % water dispersible granule (WG) (7 g kg-1) (a synthetic insecticide) was more effective in suppressing aphids, leafhoppers, whiteflies and thrips, maintaining near-zero aphid populations for 5 weeks. Application of NE at 5, 7 and 10 mL kg-1 showed a dose-dependent improvement and closely matched thiamethoxam in action at 10 mL kg-1 by reducing whitefly and thrips populations. This is the first report of using azadirachtin NE as a seed treatment in cotton. Although synthetic treatments ensured longer persistence, the azadirachtin nanoformulation offers a promising, eco-friendly, sustainable option for Integrated Pest Management (IPM).